An exploration of the value of the personal doctor-patient relationship in general practice. - Kearley, K; Freeman, G; Heath, A (2001)
BACKGROUND: Within the context of general practice, continuity of care creates an opportunity for a personal doctor-patient relationship to develop which has been associated with significant benefits for patients and general practitioners (GPs). Continuity of care is, however, threatened by trends in the organisational development of primary health care in the United Kingdom and its intrinsic role within general practice is currently the subject of debate. AIMS: To determine how many patients report having a personal doctor and when this is most valued, to compare the value of a personal doctor-patient relationship with that of convenience, and to relate these findings to a range of patient, GP, and practice variables. DESIGN OF STUDY: Cross sectional postal questionnaire study. SETTING: Nine hundred and ninety-six randomly selected adult patients from a stratified random sample of 18 practices and 284 GP principals in Oxfordshire. METHOD: Qualitative interviews with patients and GPs were conducted and used to derive a parallel patient and GP questionnaire. Each patient (100 from each practice) was invited to complete a questionnaire to evaluate their experience and views concerning personal care. All GP principals currently practising in Oxfordshire were sent a similar questionnaire, which also included demographic variables. RESULTS: Overall, 75% of patients reported having at least one personal GP. The number of patients reporting a personal GP in each practice varied from 53% to 92%. Having a personal doctor-patient relationship was highly valued by patients and GPs, in particular for more serious, psychological and family issues when 77-88% of patients and 80-98% of GPs valued a personal relationship more than a convenient appointment. For minor illness it had much less value. CONCLUSIONS: Patients and GPs particularly value a personal doctor-patient relationship for more serious or for psychological problems. Whether a patient has a personal GP is associated with their perception of its importance and with factors which create an opportunity for a relationship to evolve.